"Publish SCI papers or no degree": practices of Chinese doctoral supervisors in response to the publication pressure on science students. Issue 4 (1st October 2016) - Li, Yongyan
Abstract : Publishing English papers in journals listed in Science Citation Index (SCI) has become a requirement for degree conferment for doctoral science students at many universities in China. The publication requirement engenders high pressure for doctoral students and their supervisors and shapes the politics of the relationship between the two parties. This is illustrated in the present paper which reports a study conducted at a prestigious university in east China. Focusing on the case of a research group in biochemistry led by an expert writer (the supervisor), the study aimed to find out, from the supervisor's perspective, what revising papers for the students means to him, and what the students learn as a result of their papers being revised. It is shown that the students depend on the supervisor to meet the publication requirement, and the supervisor believes an average student cannot write a publishable paper. The paper discusses the disempowering effect of the publication requirement, and concludes that there is a role for a course on academic English writing, and that the focus on "publishing SCI papers or no degree" should be shifted at the policy level and long-term planning should go into the training of EAP-qualified language professionals.